STRATEGIC PORTFOLIO MANAGEMENT FOR PHARMACEUTICAL SOES: A COMPARATIVE STUDY OF NPD MANAGEMENT IN INDONESIA’S JKN ERA - Maria Rezitadina; Utomo Sarjono Putro (RADJA PUBLIKA, 2026)
According to Indonesia's Ministry of State-Owned Enterprises' strategic mandate, all SOEs, including pharmaceutical firms, are required to create economic value. However, pharmaceutical SOEs consistently underperform private and multinational competitors financially, a trend persisting both pre- and post-COVID-19 despite overall industry growth and the challenging JKN pricing system. The 2020 formation of a pharmaceutical SOE holding aimed to boost national resilience, product availability, and innovation, but after four years, financial improvement remains elusive, with the holding company, PT Bio Farma, recording losses from 2022 to 2024. Given that effective portfolio management is vital for pharmaceutical revenue sustainability, this underperformance indicates a core strategic deficiency, making New Product Development (NPD) portfolio management a critical issue. This research employs a mixed-method approach—benchmarking against private and multinational firms, VRIO analysis, and SWOT/TOWS synthesis—to identify structural gaps in strategic evaluation, decision-making, and capability alignment within SOEs. The findings culminate in a Strategic Blueprint proposing the establishment of a central Strategic Portfolio Management Office (SPMO) at the holding level, supported by subsidiary Project Management Offices (PMOs). The blueprint introduces a standardized NPD evaluation framework designed to enhance decision rigor, ensure strategic fit, and align subsidiary activities with core capabilities. This study contributes to strategic management literature by offering a practical, competitive strategy blueprint to improve SOE competitiveness in a regulated, high-pressure market.